Gender, Region, and Background-Related Factors Influencing Adolescent Disease-Prevention Behavior during the Covid-19 Pandemic in Indonesia - Seniwati, Tuti; Hariati, Suni; Erika, Kadek Ayu (Fakultas Ilmu-ilmu Kesehatan, 2022)
Raising awareness about disease prevention behavior in adolescents is an effective measure for reducing the transmission of COVID-19. This study aimed to examine adolescent disease-prevention behavior during the COVID-19 pandemic in Indonesia and identify its associations with gender, region, and background-related factors. This was a cross-sectional study that involved 492 respondents between the ages of 12 to 18 years and currently attending junior high school or senior high school. The Mann–Whitney U test and Kruskal–Wallis H test was used. The findings indicated that the mean age of the respondents was 15.77 (SD = 1.42), the majority of the respondents were girls (76.4%), and most were living in Eastern Indonesia (81.5%). Girls placed a significantly higher effort for prevention than boys for self-precaution, social distancing, and following coughing and sneezing etiquette, with mean (SD) values of 21.48 (SD = 2.79), 20.40 (SD = 2.89), and 17.73 (SD = 2.44), respectively. Gender and region also had significant correlations with reported self-protection, social distancing, and self-immunity enhancement behavior (p< 0.05). It can be concluded that COVID-19-prevention measures practiced by adolescents differ according to gender, region, education level, both parents’ education level, and the father’s occupation.